#TITLE_ALTERNATIVE# - PRIMA (NIM 10104004), RAPHON
Car insurance industry is one general insurance industry which grows rapidly in Indonesia. Each policy holder is guaranteed financial compensation by the car insurance company, due to damage or lost, according to a contract. Insurance company must set aside some fund to meet its liabilities. For that purpose, the insurance company needs to estimate its aggregate loss. Aggregate loss is the total loss which must be accounted for by the insurance company in a fixed time period. Two variables which determine aggregate loss are the number of claims and the amount of claims. In each different time period, the number of claims and the amount of claims may be different according to the characteristics of the policy holders in each period. In this final project, aggregate loss of one particular car insurance company is analyzed using compound distribution model. The final project gives the probability density function and distribution function of the model, considered a good fit to the data analyzed. Furthermore, it also gives the estimates of the mean and standard deviation of the aggregate loss.